2012
DOI: 10.1038/nrg3243
|View full text |Cite
|
Sign up to set email alerts
|

The continuing value of twin studies in the omics era

Abstract: The classical twin study has been a powerful heuristic in biomedical, psychiatric and behavioural research for decades. Twin registries worldwide have collected biological material and longitudinal phenotypic data on tens of thousands of twins, providing a valuable resource for studying complex phenotypes and their underlying biology. In this Review, we consider the continuing value of twin studies in the current era of molecular genetic studies. We conclude that classical twin methods combined with novel tech… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
260
0
5

Year Published

2012
2012
2020
2020

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 327 publications
(276 citation statements)
references
References 150 publications
1
260
0
5
Order By: Relevance
“…In the young twin cohort, we have collected detailed phenotypic and genetic information for both the twin individuals and their parents, making it possible to establish an extension of the twin model (which incorporates data from twins and their parents) for genetic research. It is increasingly recognized that newly identified short nucleotide polymorphisms (SNPs) from traditional case-control GWASs only explain a small proportion of heritability in disease (van Dongen et al, 2012). By contrast, family-based association analysis (i.e., combining linkage and association analysis) based on the extended twin model offers a new analytic approach to identify cause of human variation.…”
Section: Genetic Research Using Family-based Association Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…In the young twin cohort, we have collected detailed phenotypic and genetic information for both the twin individuals and their parents, making it possible to establish an extension of the twin model (which incorporates data from twins and their parents) for genetic research. It is increasingly recognized that newly identified short nucleotide polymorphisms (SNPs) from traditional case-control GWASs only explain a small proportion of heritability in disease (van Dongen et al, 2012). By contrast, family-based association analysis (i.e., combining linkage and association analysis) based on the extended twin model offers a new analytic approach to identify cause of human variation.…”
Section: Genetic Research Using Family-based Association Analysismentioning
confidence: 99%
“…Given that monozygotic (MZ) twins are perfectly matched for age, sex, and genetic background, and partly for early environmental influences, the study of discordant MZ twins may offer novel insight into DNA variant, epigenetic variation and environmental effects associated with eye diseases and quantitative traits (van Dongen et al, 2012). We are working on epigenetic variation for myopia and glaucoma, and in the meantime, looking for funding and collaborators in this area.…”
Section: Discordant Twins Studymentioning
confidence: 99%
“…Numerous studies have shown a wide variation in heritability of age-related phenotypes (Steves et al, 2012), but little is known about the extent of shared genetic effects on different systems. Similarly, the degree to which environmental factors impact upon aging trends in various body systems is unknown.Twin studies can investigate the causes of variation in a population (van Dongen et al, 2012). Identical (MZ) twins share virtually all of their variable DNA sequence, while non-identical (DZ) twins share on average only half of their segregating genes.…”
mentioning
confidence: 99%
“…Twin studies can investigate the causes of variation in a population (van Dongen et al, 2012). Identical (MZ) twins share virtually all of their variable DNA sequence, while non-identical (DZ) twins share on average only half of their segregating genes.…”
mentioning
confidence: 99%
“…However, it is also well known from epidemiological studies that certain environmental factors have a strong influence on cancer risk, for example tobacco smoking and UV sunlight exposure. In order to quantify this nongenetic effect, the unique power of human twin studies has been fundamental [6].…”
mentioning
confidence: 99%